Diet overlap of the invasive House Sparrow and the native Rufous-collared Sparrow in an agroecosystem of Central Coast of Peru - Menacho, Katherine (2018)
We analyse the diet overlap of two species of sparrows in an agroecosystem of the Central Coast of Peru, one of the species is invasive House Sparrow, while the other is native Rufous-collared Sparrow. We show that although native species has a more diverse diet (H'= 2.07), than invasive species (H' = 1.63), they present high similarity between them (Dmax = 0.15, p> 0.05). The Schoener index was ɸ = 0.73 and together with the non-metric multidimensional scaling analysis they show a broad diet overlap of both sparrows in the different months of evaluation. These results allow to conclude that there is a potential impact of the invasion of House Sparrow on the native species Rufous-collared Sparrow by food overlap.